Exploring the Correlation Between Fibrosis Biomarkers and Clinical Disease Severity in PLN p.Arg14del Patients - van der Voorn, Stephanie M.; Bourfiss, Mimount; te Riele, Anneline S. J. M.; Taha, Karim; Vos, Marc A.; de Brouwer, Remco; Verstraelen, Tom E.; de Boer, Rudolf A.; Remme, Carol Ann; van Veen, Toon A. B. (Frontiers in Cardiovascular Medicine, 2022)
Background: Pathogenic variants in phospholamban (PLN, like p. Arg14del), are found in patients diagnosed with arrhythmogenic (ACM) and dilated cardiomyopathy (DCM). Fibrosis formation in the heart is one of the hallmarks in PLN p.Arg14del carriers. During collagen synthesis and breakdown, propeptides are released into the circulation, such as procollagen type I carboxy-terminal propeptide (PICP) and C-terminal telopeptide collagen type I (ICTP). Aim: To investigate if PICP/ICTP levels in blood are correlative biomarkers for clinical disease severity and outcome in PLN p.Arg14del variant carriers. Methods: Serum and EDTA blood samples were collected from 72 PLN p.Arg14del carriers (age 50.5 years, 63% female) diagnosed with ACM (n = 12), DCM (n = 14), and preclinical variant carriers (n = 46). PICP levels were measured with an enzyme-linked immune sorbent assay and ICTP with a radio immuno-assay. Increased PICP/ICTP ratios suggest a higher collagen deposition. Clinical data including electrocardiographic, and imaging results were adjudicated from medical records. Results: No correlation between PICP/ICTP ratios and late gadolinium enhancement (LGE) was found. Moderate correlations were found between the PICP/ICTP ratio and end-diastolic/systolic volume (both rs = 0.40, n = 23, p = 0.06). PICP/ICTP ratio was significantly higher in patients with T wave inversion (TWI), especially in leads V4–V6, II, III, and aVF (p < 0.022) and in patients with premature ventricular contractions (PVCs) during an exercise tolerance test (p = 0.007). Conclusion: High PICP/ICTP ratios correlated with clinical parameters, such as TWI and PVCs. Given the limited size and heterogeneity of the patient group, additional studies are required to substantiate the incremental prognostic value of these fibrosis biomarkers in PLN p.Arg14del patients.